2019
DOI: 10.1109/tgcn.2019.2908409
|View full text |Cite
|
Sign up to set email alerts
|

Collision Resolution Protocol for Delay and Energy Efficient LoRa Networks

Abstract: Future 5G and Internet of Things (IoT) applications will heavily rely on long-range communication technologies such as low-power wireless area networks (LPWANs). In particular, LoRaWAN built on LoRa physical layer is gathering increasing interests, both from academia and industries, for enabling low-cost energy efficient IoT wireless sensor networks for, e.g., environmental monitoring over wide areas. While its communication range may go up to 20 kilometers, the achievable bit rates in LoRaWAN are limited to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…• Some device's data transmission would interfere with the FBP reception of other devices, for example, in PP2, the FBP reception at ED2 is interfered by the transmitted signal of ED1. If the distance between ED1 and 2 is far enough, FBP still can be correctly decoded due to the capture effect [24]. However, if ED1 is close to ED2, correct decoding of FBP is obstructed.…”
Section: Access Proceduresmentioning
confidence: 99%
“…• Some device's data transmission would interfere with the FBP reception of other devices, for example, in PP2, the FBP reception at ED2 is interfered by the transmitted signal of ED1. If the distance between ED1 and 2 is far enough, FBP still can be correctly decoded due to the capture effect [24]. However, if ED1 is close to ED2, correct decoding of FBP is obstructed.…”
Section: Access Proceduresmentioning
confidence: 99%
“…This is to retain the practicality of simulations given the considered high number of nodes. R ch in constraint (14), is the retransmission of lost packets due to bad channel condition for nodes n i located at distances further than d 0 from the GW.…”
Section: Min T Ec(k)mentioning
confidence: 99%
“…This led to the strive of a number of research bodies and industrial organisations to challenge the efficiency of LoRaWAN. For example, Rachkidy et al [14], proposed a collision resolution technique that allows LoRa gateway to decode the collided and hence, corrupted received packets. While Liao et al [15], introduced a multi-hop based concurrent transmission technique in order to mitigate the probability of simultaneous packets transmissions of LoRa nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CR-MAC Protocol outperforms the conventional LoRaWAN protocol in terms of throughput, energy consumption, and delay. A comparison of both the protocols can be carried out by using the simulator which is designed in Perl [28]. Simulation results showed that LoRaWAN gives the throughput 40% while CR-MAC protocols reach its throughput to 58 %, 78%, and 83% by using the two, four, and eight slots, respectively.…”
Section: Adc Mac Protocolmentioning
confidence: 99%